2014
DOI: 10.1111/cod.12304
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based training as primary prevention of hand eczema in a population of hospital cleaning workers

Abstract: Data indicates a positive effect of a low-cost on-site educational intervention for hospital cleaners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…6 The prevalence of hand eczema among hospital workers in countries other than India ranges from 6% to 80%. [7][8][9][10][11][12][13][14][15][16][17][18] However, most studies on hand eczema have been based on self-reported surveys, and have utilized varied outcome measures, and almost no epidemiological data on hand eczema among healthcare workers exist in India.…”
Section: Introductionmentioning
confidence: 99%
“…6 The prevalence of hand eczema among hospital workers in countries other than India ranges from 6% to 80%. [7][8][9][10][11][12][13][14][15][16][17][18] However, most studies on hand eczema have been based on self-reported surveys, and have utilized varied outcome measures, and almost no epidemiological data on hand eczema among healthcare workers exist in India.…”
Section: Introductionmentioning
confidence: 99%
“…Training and education may be effective at preventing OSD [Nicholson et al ]. Several groups have developed and tested primary prevention training programs for OSD among workers and secondary prevention programs for patient populations [Schwanitz et al, ; Ibler et al, ; Wilke et al, ; Clemmensen et al, ]. In Germany, extensive courses have been developed to educate workers with OSD by teaching theory and practical exercises that serve to improve prognosis and prevent OSD progression [Schwanitz et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect could be seen on behavior, knowledge, and decrease in skin symptoms when re-investigated after 3 months [29].…”
Section: Management and Preventionmentioning
confidence: 93%